Monthly Report: An Instrument for Recording the Concentration of Mustard Gas in Air - Beckman, Arnold O. (1943)
The report discusses work performed between September 20 and October 31, 1943, under contract number OEMsr-674. Beckman reported beginning construction of the first model of an instrument to record concentrations of mustard gas (H).
Keywords: Beckman, Arnold O.; Gases--Analysis; Mustard gas; Chemical agents (Munitions); United States. Office of Scientific Research and Development. National Defense Research Committee; Chemical warfare